Effect of parity, lactation stage and udder morphology on milk yield and milk constituents in Jaffarabadi buffaloes (Indian Journal of Animal Production and Management, 2024)
The present study was conducted to know the effect of parity, stage of lactation and udder morphology  on milk yield and milk constituents in Jaffarabadi buffaloes. A total of 150 buffaloes selected from private  dairy farms located in and around Hyderabadwere utilized. The average daily milk yield (ADMY) recorded  in buffaloes with different parities were 7.06 ± 0.16, 8.11 ± 0.11, 8.86 ± 0.12and 8.23 ± 0.08 Kg in first, second, third and fourth parity, respectively showing the third parity animals yielded higher ADMY compared  to other parities. The ADMY in different lactation stages recorded were 8.55 ± 0.14, 8.23 ± 0.12 and 8.08 ±  0.13 Kg in early, mid and late stage of lactation, respectively showing there was a decrease in ADMY from  early to late stage of lactation. There was a positive and highly significant (P
Keywords: Jaffarabadi buffalo; Lactation stage; Milk Constituents; Mil Yield; Parity